Impact of Covid-19 on Stock Return, Stock Liquidity and Share Price Volatility on IDX30 Index - Nur Kamri Hardi; Pardomuan Sihombing (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The first Covid-19 case in Indonesia was announced on March 2, 2020. This study aims to analyze the effect of the Covid-19 outbreak on stock returns, stock liquidity and stock price volatility on the IDX30 Index. The population in this study are 30 companies listed on the IDX30 Index for the period February 2020 - July 2020. The sampling technique used was purposive sampling. Data collection is done by documenting the required data on the capital market website. The data analysis technique used is the normality test using Jarque Bera and hypothesis testing using the Paired Sample T-Test which is processed using the EViews 12 application. The results of this study indicate that there is no difference in IDX30 stock returns before and after the announcement of the first Covid-19 case in Indonesia. As for stock liquidity and stock price volatility, there are differences before and after the announcement of the Covid-19 case.